Non-human Primate Macaca mulatta as an Animal Model for Testing Efficacy of Amixicile as a Targeted Anti-periodontitis Therapy - Gui, Qin; Lyons, Denver J.; Deeb, Janina Golob; Belvin, B. Ross; Hoffman, Paul S.; Lewis, Janina P. (Frontiers in Oral Health, 2021)
Periodontitis is an inflammatory condition triggered by selected oral microbiota, thus treatment strategies should be aimed at reducing the abundance of the pathogenic bacteria. An obstacle to pre-clinical testing of such strategies is availability of reliable animal models. Here, non-human primate (NHP), Macaca mulatta, was used to examine the effectiveness of a novel antimicrobial, amixicile, that inhibits pyruvate-ferredoxin oxidoreductase (PFOR) present in anaerobic bacteria. Animals were assessed for their periodontal health, including radiography, clinical attachment loss (CAL), presence of plaque (PI), bleeding on probing (BOP) and pocket depth (PD), and sampled for saliva, gingival crevicular fluid (GCF), and subgingival plaque to determine their baseline clinical status. Amixicile was then administered for two weeks (40mg/kg/day) and animals were monitored for periodontal health immediately after the antibiotic treatment, 1 month-, 3 months -, and 6 months post-treatment. Microbial species present in plaque and saliva were determined through 16S rDNA sequencing. Baseline assessment of the microbiome has shown significant proportion of bacteria belonging to the Streptococcus, Haemophilus, Porphyromonas, Gemella, and Fusobacterium genera. The abundance of Porphyromonas and Fusobacterium was reduced following treatment with amixicile while that of Escherichia, Haemophilus, and Gemella were elevated. CAL, PD and BOP were also significantly reduced following the treatment. In conclusion, the NHP model proves useful for pre-clinical studies of strategies targeting selected members of the oral microbiome. We show that amixicile reduces the levels of anaerobic bacteria under in vivo conditions, correlating with reduction in CAL, PD and BOP, thus validating its usefulness as an anti-microbial strategy.